(untitled) (Heritage, 2022)
The path to establishing a specialized music education with solfeggio teaching, as a necessary subject for acquiring primary, and then secondary and higher musical education, was a difficult one due to the historical turmoil on the territory of Serbia and its’ overall significant lag behind the rest of Europe in many aspects of national, cultural and educational development. Bearing in mind the lack of musically educated staff and the absence of a national composition practice, which would pave the way and open the door to the institutionalization of music education, the question of the origin of the national solfeggio school and its development arises. The aim of the paper is to observe the critical moments in the development of solfeggio teaching in the Republic of Serbia, including the actions of personalities from the field of music pedagogy spaning from the nineteenth century till present day, with particular reference to the most prevalent methodological approach.